Meningkatkan Kreatifitas Siswa PAUD Melalui Kegiatan Mewarnai di PAUD Al-Madina Desa Sesulu - Nofansyah; Latumeten, Anna Anganita Theresia; Putri, Octa Rizki Silvana (LPPM UNINUS, 2024)
This article highlights how coloring activities can help increase children’s creativity and express children’s imagination about the objects and plants around them, especially at Early Childhood Education in Al-Madina, Desa Sesulu, North Penajam Paser Regency. Through this coloring method, children can get the opportunity to express themselves and create something new. It is also expected to train children to focus on tasks and complete them well, as well as to increase confidence, a sense of satisfaction, and pride in seeing the results of their work. By providing the right opportunities and stimulation, children can optimally develop their creative potential within them. Keywords: Childhood, Coloring, Creativity, Education